2019
DOI: 10.25134/jrka.v4i2.1693
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Solvabilitas, Profitabilitas Dan Ukuran Perusahaan Terhadap Perataan Laba

Abstract: This study aimed to know the influence of slovency, probability and size company of income smoothing in the sector industrial goods comsumption listed on the indonesian stock exchange. This research is based on theories such as Agency Theory which explains that the practice of income smoothing is influenced by the conflict of interest between the management (agent) and the owner (principal) that arises when each party seeks to achieve or maintain the desired level of prosperity. The sample in this study is det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
3
1
4
Order By: Relevance
“…The results of this study are consistent with the results of research Widana & Yasa (2013) who find that company size has no significant effect on income smoothing. However, it is different from the results of Sari & Kristanti (2015), Hakim (2018) who found that company size has a positive and significant effect on income smoothing practices.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…The results of this study are consistent with the results of research Widana & Yasa (2013) who find that company size has no significant effect on income smoothing. However, it is different from the results of Sari & Kristanti (2015), Hakim (2018) who found that company size has a positive and significant effect on income smoothing practices.…”
Section: Discussioncontrasting
confidence: 96%
“…Thus, managers are motivated to do income smoothing actions to show that the company's performance is good. The results of this study are in line with the research results of Sari & Kristanti (2015), Peranasari & Dharmadiaksa (2014) and Algery (2013) who find that profitability has a positive and significant effect on income smoothing practices. However, it is different from the results of research by Natalie and Astika (2016) and Pratiwi and Handayani (2014) who find that profitability has no significant effect on income smoothing.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Semakin tinggi profitabilitas yang dihasilkan maka akan semakin baik karena menunjukan bahwa perusahaan mampu mengelola modalnya dengan baik sehingga dapat menghasilkan laba yang optimal. Hal ini sejalan dengan penelitian yang dilakukan oleh (Jamaludin, 2020) dan (Fitri & Mildawati, 2018) bahwa profitabilitas tidak mempengaruhi akitivitas penghindaran pajak. Dengan rata-rata profitabilitas sampel 10,26%, mengidentifikasikan perusahaan yang menjadi sampel penelitian tidak melakukan penghindaran pajak karena memiliki profitabilitas yang relatif rendah dimata investor hal ini menunjukkan bahwa rata-rata profitabilitas yang rendah dapat mengindikasikan bahwa Perusahaan tidak melakukan penghindaran pajak dikarenakan laba yang dihasilkan pada sampel ini rendah.…”
Section: Uji Hipotesisunclassified